Provision by a University of the Conditions for the Digital Competencies and Skills of Students and Their Legal Regulation in Local Acts - Olga A. IVANOVA; Svetlana B. VERESHCHAK; Anton K. KUZNETSOV (Communications of International Proceedings, 2021)
The digital transformation of various spheres of the society and state livelihoods poses new challenges to the sphere of higher education: the formation of digital competence among students, the ability to provide the economy with personnel having competencies to work in the digital society conditions. The purpose of the study is to analyze the relevant problems of the conditions creation by a university for the digital competencies and skills of using digital technologies formation among students, their reflection in educational programs; to consider the problems and the prospects of legal regulation in the local legal acts of a university of the concept of the digital competencies development among students and formulate appropriate recommendations. The research is based on an interdisciplinary approach. The methodological basis of the research consists of general scientific and private scientific methods of cognition. The methodological tools are selected taking into account the specific purposes of the study. The article analyzes the main digital competencies, the concept and types of digital competence, their content. A set of basic measures for the formation of digital competencies and the development of digital competence within the educational process is proposed. The authors note that timely and adequate legal support of the university digital transformation processes is an important task, in this connection, key approaches to the formation, development and measurement of students' digital competencies might be reflected in the corresponding University Concept. The development of a unified methodological approach of a university to the requirements for the formation of digital competencies and digital competence within the educational process, its adequate legal regulation, lays the foundation for the demand for future graduates of the university in the labor market, employers' satisfaction with the quality of graduates’ training and strengthens the position of a university in the market of educational services.
Keywords: Digital competencies; digital technologies in education; digitalization of higher education; digital educational environment; digital University